Dietary diversity and nutrition status of preschool children from banana dependent households in Gitega (Burundi) and Butembo (Democratic Republic of Congo) - Ekesa, B.; Garming, H.; Blomme, Guy (2011)
A cross-sectional survey was carried out in Gitega health zone (Burundi) and Butembo health zone (Democratic Republic of Congo, DRC) with the objective of establishing dietary diversity and nutritional status of pre-school children from rural-banana dependent households. The two health zones were selected based on high dependency on bananas and plantains and the high levels of food insecurity. Through multi-stage random sampling commune/collectivity, colline/localite and villages were selected from each of the health zones; household listing was done in each of the sub-sites and systematic random sampling used to select 281 households with pre-school children (Butembo- 138 and Gitega- 143). Findings showed that 48% and 42% of the children from Butembo (DRC) and Gitega (Burundi) respectively had consumed food items from less than 3 food groups. Only 7% and 29% of children from Butembo (DRC) and Gitega (Burundi), respectively had consumed highly diversified diets (>6 food groups). The other popular food groups were; vegetables group, cereals and grains group in Gitega (Burundi) and vegetables group and legumes group in Butembo (DRC). In both countries less than 15% of the preschool children consumed food from meat, eggs or milk groups.